Deformation of stainless steel cables at elevated temperature. (15th May 2020) - Sun, Guojun; Li, Xiaohui; Wu, Jinzhi; Chen, Ronghua; Chen, Guangning
Highlights: Thirty stainless steel cables tested at elevated temperatures. Thermal expansion coefficient of the stainless steel cables. Equation relating the deformation of the cables and the temperature and initial stress. Parameters of the Field & Field creep model for the stainless steel cables. Abstract: The deformation of stainless steel cables at elevated temperatures is an important consideration for the design of fire resistant pre-stressed spatial structures. In this paper, by conducting extensive experiments on a number of specimens, the thermal expansion under a stress-free state, the deformation under thermo-mechanical coupling state in transient heating stage, and the creep deformation in constant temperature stage of stainless cables subjected to elevated temperature were studied experimentally. A correlation for the thermal expansion coefficient of the stainless steel cables in the range of 30–600 °C was obtained. In addition, an equation relating the deformation of the cables and the temperature and initial stress under the thermo-mechanical coupling state in the heating stage was proposed. Furthermore, the relationship between the parameters of the Field & Field creep model and the temperature was derived for the stainless steel cables.